EKSISTENSI MAJALAH GATRA SUMATERA BAGIAN SELATAN MENGHADAPI ERA DIGITALISASI 4.0 - Isna Wijayani; Karerek Karerek (Universitas Baturaja, 2021)
ABSTRACT This research is entitled The Existence of Gatra Magazine of Sumbagsel Facing the Era of Digitization 4.0. With the formulation of the problem: How does the existence of Gatra Sumbagsel Magazine face the era of digitization 4.0. The type of research itself uses descriptive qualitative methods with primary data sources from interviews and secondary data sources from observation and documentation. In analyzing the data, it is carried out through three stages, namely: reduction, data presentation and data verification or drawing conclusions. Data analysis was performed using SWOT analysis and Mass Media Management theory. The results showed that Gatra Sumbagsel Magazine was able to compete in the digitization era by implementing a lean business pattern of human resources in maintaining branding and maximizing business potential in government and private institutions as the main target of business development. Keywords: Existence, Magazine, Digitization Era